Municipal development and infrastructure index and its relationship with child mortality in brazilian municipalities (Research, Society and Development, 2020)
The objective of this study is to study the measurement and distribution of quality of life through the construction of an index for the Brazilian municipalities in the year of 2010 and to observe its spatial autocorrelation with the infant mortality rate. For that, we used factorial analysis and exploratory spatial data analysis. The results point to the existence of strong heterogeneity in the development of Brazilian municipalities. The municipalities of the North, Northeast and Center-West regions that are surrounded by municipalities with a high average of infant deaths, presented the lowest rate of development, which confirms the high socioeconomic disparity in the Brazilian regions.